Revisiting Heparin-Induced Thrombocytopenia among Patients Undergoing Free Tissue Transfer: A Systematic Review - Yamin, Mohammed; Tobin, Micaela; Raquepo, Tricia; Park, John B.; Lee, Daniela; Escobar-Domingo, Maria J.; Foppiani, Jose; Fanning, James E.; Zhu, Eric; Posso, Agustin N.; Ma, Haobo; Lin, Samuel J.; Lee, Bernard T.; Cauley, Ryan P. (Journal of Reconstructive Microsurgery, 2025)
Heparin is frequently used to mitigate the risk of thrombosis in microsurgical free tissue transfer. Although rare, heparin-induced thrombocytopenia (HIT) is a severe, life-threatening complication that can arise in patients exposed to heparin products. This systematic review aims to examine patterns in demographics, flap characteristics, diagnostic approaches, and treatment protocols for HIT following free flap reconstruction.A systematic search was conducted across PubMed, MEDLINE, and Web of Science, following Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines. Search terms included “heparin-induced thrombocytopenia,” “HIT syndrome,” “free flaps,” “microsurgery,” “plastic surgery,” and “reconstructive surgery.” Case reports or series written in English that presented patients developing HIT following free flap procedures were included. Eligibility criteria are accessible on the International Prospective Register of Systematic Reviews (PROSPERO; CRD42025650125).A total of 15 articles were included, encompassing a total of 23 free flap reconstruction cases. The median patient age was 52 years, with male predominance (69.6). Lower extremity reconstruction was most common (47.8%), primarily using anterolateral thigh flaps (39.1%). Median 4T score was 6, median time to HIT diagnosis was 6 days, and median nadir platelet count was 72 × 103/μL. Thrombotic complications were common, with venous thrombosis (34.8%) predominating. Argatroban (26.1%) was the most frequently used alternative anticoagulant, while warfarin (30.4%) was the most common discharge medication. Overall flap survival was 43.5%. Meta-analysis revealed no significant difference in flap survival between anticoagulation strategies (95% CI: 0.38–2.63, p = 1.000).HIT represents a rare but devastating complication in free flap reconstruction, with approximately half of the affected flaps failing despite intervention. Although no single anticoagulation strategy demonstrated superior outcomes, expeditious diagnosis and treatment may improve flap salvage rates. This review provides a foundation for developing standardized protocols for HIT management in microsurgical patients.
Keywords: heparin-induced thrombocytopenia; microsurgery; free flap